Tradisi dan Budaya Kasepuhan Ciherang: Suatu Kajian Kearifan Lokal Masyarakat Banten Kidul - Heryatun, Yayu; Rosadi, Rosadi; Mildaniati, Mildaniati; Majid, Chelsea Rafidah; Delvianti, Seety (UIN SIber Syekh Nurjati Cirebon, 2025)
Kasepuhan Ciherang is one of the Kaolotan or Kasepuhan in South Banten. Precisely in Ciherang Village, Ciherang Village, Cibeber District, Lebak Regency, Banten Province. Kasepuhan Ciherang has a unique cultural treasure, a culture with a lot of local wisdom. There are many cultural activities such as the Nadar ritual, the Seren Ritual, the Earth Alms Ritual and others. The characteristics of the Ciherang community are also known as communities with Huma or farming areas. The community carries out the annual Seren Taun ceremony as part of the ceremony for the annual rice harvest party which is held as an expression of gratitude for the year's harvest. The Seren Taun ritual is also closely related to respect for Nyai Sri Pohaci or Dewi Sri. The people of Ciherang know her as Dewi Sri or Nyi Sri Pohaci Sanghyang Asri, who is known as the Goddess of Rice and a symbol of soil and plant fertility, especially the rice plant